Математичні моделі хімічних процесів зі змінними характеристиками - Іглін, Сергій Петрович (Національний технічний університет "Харківський політехнічний інститут", 2023)
Розглядається побудова математичних моделей складних хімічних процесів, коли в різні моменти часу на результат хімічної реакції діють різні чинники. Використовується метод найменших квадратів. Цей матеріал може бути використаний для навчання студентів ЗВО в дисциплінах Математична статистика, Чисельні методи, Загальні технології харчових виробництв, Харчова хімія та ін. Приклади з аналізу експериментальних моделей дослідження лабораторних випробувань нових кислотних компонентів для карбонатного колектора можуть бути застосовані у навчанні студентів за ОП Хімічна інженерія.

The article discusses the construction of athematical models of complex chemical processes when different factors act on the result of a chemical reaction at different points in time. The method of least squares is used. This material can be used to teach university students in the disciplines of Mathematical Statistics, Numerical Methods, General Technologies of Food Production, Food Chemistry, etc. Applications from the analysis of experimental research models and laboratory testing of innovative technologies for the development of different types of galusa can be supported by incoming students in the chemical engineering program. Examples from the analysis of experimental research models of laboratory tests of new acid components for a carbonate collector can be applied in the training of students in the Chemical Engineering educational program.
Mathematical models of chemical processes with variable characteristics
Keywords: математична модель; аналітичний вираз; точка перемикання; метод найменших квадратів; мінімізація функції; mathematical model; analytic expression; switching point; least squares method; function minimization